Targeted Mutagenesis in Pathogenic Leptospira Species: Disruption of the LigB Gene Does Not Affect Virulence in Animal Models of Leptospirosis - Croda, Julio (American Society for Microbiology (ASM), 2008)
The pathogenic mechanisms of Leptospira interrogans, the causal agent of leptospirosis, remain largely unknown. This is mainly due to the lack of tools for genetically manipulating pathogenic Leptospira species. Thus, homologous recombination between introduced DNA and the corresponding chromosomal locus has never been demonstrated for this pathogen. Leptospiral immunoglobulin-like repeat (Lig) proteins were previously identified as putative Leptospira virulence factors. In this study, a ligB mutant was constructed by allelic exchange in L. interrogans; in this mutant a spectinomycin resistance (Spc(r)) gene replaced a portion of the ligB coding sequence. Gene disruption was confirmed by PCR, immunoblot analysis, and immunofluorescence studies. The ligB mutant did not show decrease virulence compared to the wild-type strain in the hamster model of leptospirosis. In addition, inoculation of rats with the ligB mutant induced persistent colonization of the kidneys. Finally, LigB was not required to mediate bacterial adherence to cultured cells. Taken together, our data provide the first evidence of site-directed homologous recombination in pathogenic Leptospira species. Furthermore, our data suggest that LigB does not play a major role in dissemination of the pathogen in the host and in the development of acute disease manifestations or persistent renal colonization.